Distinct changes in cAMP and extracellular signal-regulated protein kinase signalling in L-DOPA-induced dyskinesia. - Emanuela Santini (Public Library of Science (PLoS), 2010)
Background In rodents, the development of dyskinesia produced by L-DOPA in the dopamine-depleted striatum occurs in response to increased dopamine D1 receptor-mediated activation of the cAMP - protein kinase A and of the Ras-extracellular signal-regulated kinase (ERK) signalling pathways. However, very little is known, in non-human primates, about the regulation of these signalling cascades and their association with the induction, manifestation and/or maintenance of dyskinesia. Methodology/results We here studied, in the gold-standard non-human primate model of Parkinson's disease, the changes in PKA-dependent phosphorylation of DARPP-32 and GluR1 AMPA receptor, as well as in ERK and ribosomal protein S6 (S6) phosphorylation, associated to acute and chronic administration of L-DOPA. Increased phosphorylation of DARPP-32 and GluR1 was observed in both L-DOPA first-ever exposed and chronically-treated dyskinetic parkinsonian monkeys. In contrast, phosphorylation of ERK and S6 was enhanced preferentially after acute L-DOPA administration and decreased during the course of chronic treatment. Conclusion Dysregulation of cAMP signalling is maintained during the course of chronic L-DOPA administration, while abnormal ERK signalling peaks during the initial phase of L-DOPA treatment and decreases following prolonged exposure. While cAMP signalling enhancement is associated with dyskinesia, abnormal ERK signalling is associated with priming.